Non-fatal tractor accidents and their prevention - Suutarinen, Juha (The Haworth Medical Press, New York, 1997)
Non-fatal tractor accidents are often quite serious, resulting in disability for an average period of 26 days. The most common injuries are strains and sprains of the lower limbs and contusions of the limbs. In this study, the incidence of non-fatal tractor accidents was found not to be very high, but there are certain jobs that are relatively dangerous, where tractors are used. These include dismounting and mounting the tractor, and coupling and uncoupling implements. The most dangerous work phases can be made safer with traditional countermeasures, e.g. by developing ergonomic and engineering solutions for safety and by educating tractor users. However, more emphasis in research and consulting should be put on improving safety management on farms, because the quality of management defines the safety of operation.
Sarjan kyseinen numero on samalla toisen julkaisun osa: "Agricultural Health and Safety: Recent Advances. Part II"
Keywords: Ra; traktorit; työtapaturmat; turvallisuus; turvaohjaamot; tapaustutkimus; tractors; accidents; farm safety; research; safety measures